Chapter An Open Data platform for decision making in local public administration - Massenzio, Matteo (Proceedings e report, 2023)
This paper presents the Milan Open Data (OD) platform as a means to provide statistics and data in the framework of "Data-Driven Milan", a city where policy decisions are taken in an "informed and aware" way using data. Open Data are ever more important in providing citizen communities with useful information. Over the last 10 years, the municipality of Milan has developed its OD platform from an experimental portal to a fully-fledged portal with more than 1,600 datasets, implemented a Linked Open Data (LOD) system and 8 advanced data visualization projects, and produced OD policies and operating guidelines. The OD portal is based on the CKAN technology, which makes datasets available via both download and Application Programming Interfaces. It currently has about 9,000 unique visitors per month. Data are also published as tables on the statistical portal and maps on the geo-portal. A single entry point to the three portals is about to be released. The advanced visualization projects make data available as reader-friendly graphics. Depending on its topic, a project might be a storytelling of the city through key statistics, a means to communicate the administration's achievements, or a "data democratization" operation, such as "Open bilancio", which publishes detailed information about the municipality's annual budget. LOD are semantically enriched and machine-readable data that help to implement data interoperability between distributed systems. The ongoing LOD automation project aims to improve the current system by minimizing manual operations in the dataset lifecycle. Three Municipal Resolutions have been issued to define OD governance: the first establishes that data are released under an Open License, to promote the digital economy; the second promotes data interoperability and quality; and the third, issued in 2021, establishes the guidelines and an operating model for OD governance, including ontology-supported data publishing.